An innovative method to reduce count loss from pulse pile-up in a photon-counting pixel for high flux X-ray applications. (8th March 2017) - Lee, D.; Lim, K.; Park, K.; Lee, C.; Alexander, S.; Cho, G.
Abstract: In this study, an innovative fast X-ray photon-counting pixel for high X-ray flux applications is proposed. A computed tomography system typically uses X-ray fluxes up to 10 8 photons/mm 2 /sec at the detector and thus a fast read-out is required in order to process individual X-ray photons. Otherwise, pulse pile-up can occur at the output of the signal processing unit. These superimposed signals can distort the number of incident X-ray photons leading to count loss. To minimize such losses, a cross detection method was implemented in the photon-counting pixel. A maximum count rate under X-ray tube voltage of 90 kV was acquired which reflect electrical test results of the proposed photon counting pixel. A maximum count of 780 kcps was achieved with a conventional photon-counting pixel at the pulse processing time of 500 ns, which is the time for a pulse to return to the baseline from the initial rise. In contrast, the maximum count of about 8.1 Mcps was achieved with the proposed photon-counting pixel. From these results, it was clear that the maximum count rate was increased by approximately a factor 10 times by adopting the cross detection method. Therefore, it is an innovative method to reduce count loss from pulse pile-up in a photon-counting pixel while maintaining the pulse processing time.